Preparation method of flexible sheet and coating layer slurry
By using coating layer slurry with high solid content, low viscosity and small particle size, combined with high-speed emulsification and dispersion technology, the existing coating methods have been solved, and the stability, uniformity and electrochemical performance of the coating layer have been improved.
Patent Information
- Application Number
- CN202411840616.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing coating methods have complex processes, high cost and low efficiency, poor performance of the prepared products, and poor stability and uniformity of the coating layer.
A coating layer slurry with a solid content of 20% to 50%, a viscosity of 10 cp to 100 cp and a particle size less than 2 μm was prepared by a high-speed emulsification and dispersion process, and a stable coating layer was formed on the base film.
It achieves the improvement of the stability, uniformity and electrochemical performance of the coating layer. It has simple process, low cost and high production efficiency, and is suitable for automated continuous production.
Smart Images

Figure CN119798752A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of flexible sheet material production and coating production, and in particular to a method for preparing a flexible sheet material and a coating layer slurry. Background Art
[0002] In modern coating production technology, die extrusion coating has become a widely used coating method due to its advantages such as high precision, wide coating window and high reliability.
[0003] However, due to the fluid properties of the slurry, low-solid content slurry often has problems such as overflow, cracking, and unevenness when coated on the surface of the base film, affecting the uniformity and stability of the product. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing a flexible sheet and a coating layer slurry to solve the problems of the existing coating method, such as complex process, high cost, low efficiency, poor performance of the prepared product, poor stability and uniformity of the coating layer, etc.
[0005] To achieve the above and related purposes, the present invention adopts the following technical solutions:
[0006] The first aspect of the present invention provides a flexible sheet material, comprising a base film and a coating layer supported on the base film, wherein the coating layer is formed by coating a coating layer slurry on the base film and drying the coating layer slurry;
[0007] The coating layer slurry has a solid content of 20% to 50%, a viscosity of 10cp to 100cp, and a particle size of less than 2μm.
[0008] Furthermore, the coating layer has a thickness of 10 μm to 100 μm.
[0009] Furthermore, the precious metal loading of the flexible sheet is 0.3 mg / cm 2 ~1mg / cm 2 .
[0010] Furthermore, the coating layer slurry is prepared by high-speed emulsification and dispersion of raw materials with a viscosity of 100cp to 1000cp, and the raw materials include a reactant and a perfluorosulfonic acid resin solution.
[0011] Furthermore, in the raw materials, the mass ratio of the reactant to the perfluorosulfonic acid resin solution is (2-4):1.
[0012] A second aspect of the present invention provides a method for preparing a coating layer slurry, comprising:
[0013] (1) mixing a reactant, a perfluorosulfonic acid resin solution, an alcohol and deionized water to obtain a raw material having a viscosity of 100 cp to 1000 cp;
[0014] (2) The raw materials are emulsified and dispersed at a high speed to obtain a coating layer slurry with a solid content of 20% to 50%, a viscosity of 10 cp to 100 cp, and a particle size of less than 2 μm.
[0015] Furthermore, the active material of the reactant is selected from at least one of platinum, ruthenium, iridium and iridium oxide.
[0016] Furthermore, the linear velocity of the high-speed emulsification dispersion is 25 m / s to 60 m / s.
[0017] Furthermore, the mass ratio of deionized water to alcohol is 1:(2-5).
[0018] Furthermore, the alcohol is a low boiling point alcohol, and the alcohol is at least one selected from methanol, ethanol, n-propanol, and isopropanol.
[0019] The beneficial technical effects of the present invention are:
[0020] The coating layer slurry of the present invention has lower viscosity and smaller particle size while maintaining high solid content, and the slurry has good fluidity. The coating layer formed by coating the slurry on the base film has good stability and uniformity. The prepared flexible sheet has no cracks on the surface and good electrochemical performance.
[0021] The coating layer slurry preparation process of the present invention performs high-speed emulsification and dispersion, can disperse high-viscosity raw materials evenly and is not easy to settle and agglomerate, and obtains the coating layer slurry with good fluidity and coating uniformity.
[0022] The preparation method of the invention has simple process, low cost and high production efficiency, and is conducive to realizing automated continuous production.
[0023] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present application, and together with the specification, are used to explain the principles of the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0025] Figure 1 This is a partial enlarged effect diagram of the flexible sheet of Example 1 of the present application;
[0026] Figure 2 This is a diagram showing the coating effect of a flexible sheet in Example 1 of the present application;
[0027] Figure 3 This is a partial enlarged effect diagram of the flexible sheet of Comparative Example 1 of the present application;
[0028] Figure 4 This is a diagram showing the coating effect of the flexible sheet of Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0029] Unless otherwise defined, all technical and / or scientific terms used herein have the same meaning as the general understanding of a person of ordinary skill in the art to which the present invention belongs. It should be understood that certain features of the present invention (described in the context of separate embodiments for clarity) may also be provided in combination in a single embodiment. On the contrary, multiple features of the present invention (described in the context of a single embodiment for brevity) may also be provided separately or in any suitable combination or in any other described embodiment of the present invention when appropriate. Certain features described in the context of various embodiments will not be considered as essential features of those embodiments unless the embodiment is inoperable without those elements. The present invention is further described below by specific specific examples, but it should be noted that the specific process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention, and the protection scope of the present invention cannot be limited thereto. All equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.
[0030] The present invention provides a flexible sheet material, comprising a base film and a coating layer supported on the base film, wherein the coating layer is formed by coating a coating layer slurry on the base film and drying the coating layer slurry;
[0031] The coating layer slurry has a solid content of 20% to 50%, a viscosity of 10cp to 100cp, and a particle size of less than 2μm.
[0032] In some embodiments, the solid content of the coating layer slurry of the present application is higher than the solid content of the existing slurry (10% to 20%), and its solid content is 20% to 50%. For example, it can be 20%, 24%, 28%, 32%, 35%, but is not limited to the listed values. Other values not listed within the above numerical range are also applicable.
[0033] In some embodiments, a slurry with a higher solid content generally has a higher viscosity and is denser. Such a high-viscosity slurry may cause uneven coating or cracking during coating, especially during drying, where a high solid content may cause the coating to fall off. The coating layer slurry used in the present application has a high solid content but a lower viscosity and better fluidity, and is more likely to form a uniform coating, thereby improving the performance of the coating layer and the electrochemical properties of the flexible sheet.
[0034] In some embodiments, the surface modification referred to in this application includes but is not limited to using polymer to modify the perfluorosulfonic acid proton exchange membrane, depositing precious metal reactants on the membrane surface to modify the perfluorosulfonic acid proton exchange membrane, and using etching as a surface treatment to modify the perfluorosulfonic acid proton exchange membrane. The flexible sheet of this application can be used in the fields of industrial products, electronic products, optoelectronic product electrodes, fuel cells, etc.
[0035] In some embodiments, the coating layer slurry of the present application is coated on the base film to a thickness of 20 μm to 200 μm; after drying, the coating layer has a thickness of 10 μm to 100 μm.
[0036] In some embodiments, the precious metal loading of the flexible sheet of the present application is 0.3 mg / cm 2 ~1mg / cm 2 .
[0037] In some embodiments, the coating layer slurry of the present application is prepared by high-speed emulsification dispersion of raw materials with a viscosity of 100cp to 1000cp, and the raw materials include reactants and perfluorosulfonic acid resin solution. Since the viscosity of the raw materials of the present application is higher than that of the slurry for general flexible sheet spraying, the degree of difficulty in dispersion is also increased accordingly. The more viscous the raw materials are, the higher the dispersion speed and collision strength are required. Therefore, the present application uses a high-speed emulsification dispersion process, which is shorter in time, can achieve a smaller particle size, and has higher production efficiency than the traditional ball milling dispersion process.
[0038] Furthermore, due to the high viscosity of the raw materials in the present application, even if the traditional ball milling dispersion process is used and the ball milling is performed for a long time, the particle size of the slurry finally prepared is still higher than 2μm, such as 2.2μm, 2.5μm, etc., and its dispersion uniformity is poor and it is easy to settle and agglomerate. However, the present application uses high-speed emulsification dispersion, which can quickly disperse the raw materials into a slurry with a particle size of less than 2μm, such as 0.7μm. This small-particle slurry is easier to disperse evenly.
[0039] In some embodiments, the mass concentration of the perfluorosulfonic acid resin solution of the present application is 10% to 30%, for example, it can be 10%, 15%, 20%, 25%, 30%, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0040] In some embodiments, the mass ratio of the reactant of the present application to the perfluorosulfonic acid resin solution is (2-4):1.
[0041] The invention also provides a coating layer slurry, comprising a reactant, a perfluorosulfonic acid resin solution, alcohol and deionized water; the coating layer slurry has a solid content of 20% to 50%, a viscosity of 10cp to 100cp, and a particle size of less than 2μm.
[0042] The present invention also provides a method for preparing a coating layer slurry, comprising:
[0043] (1) mixing a reactant, a perfluorosulfonic acid resin solution, an alcohol and deionized water to obtain a raw material having a viscosity of 100 cp to 1000 cp;
[0044] (2) The raw materials are emulsified and dispersed at high speed to obtain a coating layer slurry with a solid content of 20% to 50%, a viscosity of the coating layer slurry of 10 cp to 100 cp, and a particle size of the coating layer slurry of less than 2 μm.
[0045] In some embodiments, the alcohol is a low boiling point alcohol, and the alcohol is selected from at least one of methanol, ethanol, n-propanol, and isopropanol.
[0046] In some embodiments, the mass ratio of deionized water to alcohol in the present application is 1:(2-5).
[0047] In some embodiments, the active material of the reactant of the present application is selected from at least one of platinum, ruthenium, iridium, and iridium oxide.
[0048] In some embodiments, for high-viscosity raw materials, the present application performs high-speed emulsification dispersion. The dispersed particle size is more uniform and the slurry particle size is also smaller. The slurry particle size is smaller, and it is easier to disperse more evenly and suspend, which slows down the sedimentation rate. Therefore, the present application performs high-speed emulsification dispersion at a linear speed of 25m / s to 60m / s, for example, it can be 25m / s, 30m / s, 35m / s, 40m / s, 60m / s, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0049] In some embodiments, the dispersion efficiency of the high-speed emulsification dispersion of the present application is 30mL / 10min to 200mL / min, for example, it can be 30mL / 10min, 60mL / 10min, 90mL / 10min, 120mL / 10min, 150mL / 10min, 170mL / 10min, 200mL / 10min, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0050] In some embodiments, the temperature of the high-speed emulsification dispersion of the present application is less than 50°C, and the dispersion time does not exceed 5 minutes to avoid the slurry temperature being too high and the dispersion time being too long, which may cause the perfluorosulfonic acid resin in the slurry to denature, making the slurry more viscous and easily causing uneven coating or cracking.
[0051] In some embodiments, step (2) of the present application further comprises: after the raw materials are emulsified and dispersed at high speed, stirring at 0°C to 30°C to obtain a coating layer slurry. The slurry dispersed at high speed in the present application is continuously stirred and dispersed under temperature control to prevent the slurry from settling. Further, the stirring speed of the present application is greater than 800rpm, and further, the stirring speed is between 800rpm and 2000rpm to reduce the volatilization of water and alcohol and maintain the stability of the slurry ratio.
[0052] In some embodiments, the present application can control the forming particle size and viscosity of the coating layer slurry by regulating the temperature and time of high-speed emulsification and dispersion and the linear speed of high-speed emulsification and dispersion in the preparation process of the high-solid content coating layer slurry, so that the high-solid content coating layer slurry has the advantages of low sedimentation rate and good dispersion uniformity.
[0053] The present invention also provides a method for preparing a flexible sheet, comprising coating the coating layer slurry on both sides of a base film, and drying the coating layer slurry to obtain the flexible sheet.
[0054] In some embodiments, the coating layer slurry of the present application has a lower viscosity and smaller particle size while maintaining a high solid content, the slurry has good fluidity, the coating layer formed by the slurry coated on the base film has good stability and uniformity, the prepared flexible sheet has no cracks on the surface, and has good electrochemical properties.
[0055] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0056] Example 1
[0057] (1) mixing a reactant, a perfluorosulfonic acid resin solution, methanol and deionized water to obtain a raw material with a viscosity of 100 cp;
[0058] The active substance of the reactant is platinum; the mass concentration of the perfluorosulfonic acid resin solution is 20%;
[0059] The mass ratio of the reactant to the perfluorosulfonic acid resin solution is 2:1;
[0060] The mass ratio of deionized water to methanol is 1:2.
[0061] (2) The raw materials were emulsified and dispersed at a high speed at a linear speed of 25 m / s, the dispersion temperature was less than 50°C, and the dispersion time was 4 minutes, to obtain a coating layer slurry with a solid content of 20% and a viscosity of 10 cp; the particle size of the coating layer slurry was 0.718 μm.
[0062] (3) The coating layer slurry is coated on both sides of the proton exchange membrane and then dried to obtain a flexible sheet.
[0063] Example 2
[0064] (1) mixing a reactant, a perfluorosulfonic acid resin solution, methanol and deionized water to obtain a raw material with a viscosity of 300 cp;
[0065] The active substance of the reactant is ruthenium; the mass concentration of the perfluorosulfonic acid resin solution is 20%;
[0066] The mass ratio of the reactant to the perfluorosulfonic acid resin solution is 3:1;
[0067] The mass ratio of deionized water to methanol is 1:3.
[0068] (2) The raw materials were emulsified and dispersed at a linear speed of 40 m / s, the dispersion temperature was less than 50° C., and the dispersion time was 4 minutes to obtain a coating layer slurry with a solid content of 25% and a viscosity of 50 cp; the particle size of the coating layer slurry was 0.822 μm.
[0069] (3) The coating layer slurry is coated on both sides of the proton exchange membrane and then dried to obtain a flexible sheet.
[0070] Example 3
[0071] (1) mixing a reactant, a perfluorosulfonic acid resin solution, methanol and deionized water to obtain a raw material with a viscosity of 500 cp;
[0072] The active substance of the reactant is iridium; the mass concentration of the perfluorosulfonic acid resin solution is 30%;
[0073] The mass ratio of the reactant to the perfluorosulfonic acid resin solution is 4:1;
[0074] The mass ratio of deionized water to methanol is 1:5.
[0075] (2) The raw materials were emulsified and dispersed at a high speed at a linear velocity of 65 m / s, the dispersion temperature was less than 50° C., and the dispersion time was 4 minutes to obtain a coating layer slurry with a solid content of 35% and a viscosity of 100 cp; the particle size of the coating layer slurry was 0.932 μm.
[0076] (3) The coating layer slurry is coated on both sides of the proton exchange membrane and then dried to obtain a flexible sheet.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 1 is:
[0079] The conventional ball milling dispersion process was used to disperse the particles, thereby obtaining a coating layer slurry having a solid content of 20%, a viscosity of 80 cp, and a particle size of 1.779 μm.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is:
[0082] A shear emulsifier was used to perform high-speed emulsification and dispersion at a speed of 1500 rpm to obtain a coating layer slurry with a solid content of 20%, a viscosity of 60 cp, and a particle size of 1.538 μm.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is:
[0085] The high-speed emulsification dispersion line speed was 80 m / s, and a coating layer slurry with a solid content of 20%, a viscosity of 110 cp, and a particle size of 0.684 μm was obtained.
[0086] Comparative Example 4
[0087] The difference between this comparative example and Example 1 is:
[0088] The high-speed emulsification dispersion line speed was 20 m / s, and a coating layer slurry with a solid content of 20%, a viscosity of 38 cp, and a particle size of 1.081 μm was obtained.
[0089] Comparative Example 5
[0090] (1) mixing a reactant, a perfluorosulfonic acid resin solution, methanol and deionized water to obtain a raw material with a viscosity of 50 cp;
[0091] The active substance of the reactant is platinum; the mass concentration of the perfluorosulfonic acid resin solution is 20%;
[0092] The mass ratio of the reactant to the perfluorosulfonic acid resin solution is 1:1;
[0093] The mass ratio of deionized water to methanol is 4:1.
[0094] (2) The raw materials were emulsified and dispersed at a high speed at a linear speed of 25 m / s, the dispersion temperature was less than 50°C, and the dispersion time was 4 minutes to obtain a coating layer slurry with a solid content of 10% and a viscosity of 6 cp; the particle size of the coating layer slurry was 0.520 μm.
[0095] (3) The coating layer slurry is coated on both sides of the proton exchange membrane and then dried to obtain a flexible sheet.
[0096] Performance Testing
[0097] Surface morphology of flexible sheet: The flexible sheets prepared in Example 1 and Comparative Example 1 were tested by electron microscope and observed by naked eyes. Figures 1 to 4 shown.
[0098] Flexible sheet stability: The flexible sheets prepared in Example 1 and Comparative Examples 1 to 5 were tested for stability. During the test, the current density was set to 1.6 A / cm 2 , a 50-hour stability test was conducted, and the test results are shown in Table 1.
[0099] The experimental data and analysis are as follows:
[0100] Figure 1 This is a partial enlarged effect diagram of the coating layer slurry of Example 1 after coating on the proton exchange membrane. Figure 2 This is a diagram showing the coating effect after the coating layer slurry of Example 1 is coated on the proton exchange membrane. Figure 1 for Figure 2 A partial enlargement of the proton exchange membrane is shown in Figure 1, which is a photo of the untreated coating slurry being coated on the proton exchange membrane. Figure 1 and Figure 2 It can be seen that the coating layer slurry of the present application is coated with a uniform black color, and the coating layer has no defects; when the flexible sheet is placed on the LED, it can be observed that the black coating is evenly distributed without cracks or pinhole defects.
[0101] Figure 3 This is a partial enlarged effect diagram of the coating layer slurry of Comparative Example 1 after coating on the proton exchange membrane. Figure 4 This is a diagram showing the coating effect after the coating layer slurry of Comparative Example 1 is coated on the proton exchange membrane. Figure 3 for Figure 4 A partial enlargement of the same coating slurry is a photo of the coating on the proton exchange membrane. Figure 4 and Figure 4 It can be seen that the flexible sheet prepared by the coating layer slurry obtained by traditional ball milling dispersion has obvious cracks in the coating layer. When placed on an LED lamp, obvious light cracks and pinholes can be observed around the coating layer. This is because the coating layer slurry of Comparative Example 1 has a large particle size, high viscosity, poor slurry fluidity, poor uniformity when coated on the proton exchange membrane, and cracks in the coating layer after drying.
[0102] Similarly, Comparative Example 2 uses a shear emulsifier for dispersion. Under the premise of high solid content, its emulsification efficiency is poor, and the particle size of the slurry prepared is larger than that of Example 1 of the present application, and the viscosity is relatively higher. The flexible sheet prepared from the coating layer slurry of Comparative Example 2 also has cracking phenomenon.
[0103] In comparative example 3, the line speed is too high. Under the condition of high-speed dispersion, the temperature of the slurry will exceed 50°C. At this time, the perfluorosulfonic acid resin in the slurry may be denatured, making the slurry very viscous. The viscosity of the final coating layer slurry exceeds 100cp, the coating is uneven, and it is easy to crack.
[0104] In comparative example 4, the line speed is too low, the shear force and collision strength are insufficient, the particles in the raw material are not easily broken, the dispersed particle size is uniformly reduced, and the slurry particle size is also larger. Therefore, the flexible sheet coated with the coating layer slurry also has cracks.
[0105] The coating slurry of the comparative example 5 has a low solid content, so the coating of the flexible sheet coated with the slurry has cracking, and will affect the stability of the flexible sheet.
[0106] Table 1 Stability of flexible sheets of Example 1 and Comparative Examples 1 to 5
[0107]
[0108]
[0109] It can be seen from Table 1 that after 50 hours of stability test, the voltage change rate of the flexible sheet prepared in the embodiment of the present application is less than that of the flexible sheets of Comparative Examples 1 to 5, which indicates that the flexible sheet coated with the coating layer slurry in the embodiment of the present application has better stability.
[0110] In summary, the flexible sheet prepared in the present application, even if coated with a high solid content coating layer slurry, still has a smooth surface morphology, no cracking problem, good coating layer uniformity and stability, and good electrochemical performance.
[0111] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A flexible sheet, characterized in that: The invention comprises a base film and a coating layer supported on the base film, wherein the coating layer is formed by coating a coating layer slurry on the base film and drying the coating layer slurry; The coating layer slurry has a solid content of 20% to 50%, a viscosity of 10cp to 100cp, and a particle size of less than 2μm.
2. The flexible sheet according to claim 1, characterized in that: The coating layer has a thickness of 10 μm to 100 μm.
3. The flexible sheet according to claim 1, characterized in that: The precious metal loading of the flexible sheet is 0.3 mg / cm 2 ~1mg / cm 2 .
4. The flexible sheet material according to claim 1, characterized in that: The coating layer slurry is prepared by high-speed emulsification and dispersion of raw materials with a viscosity of 100cp to 1000cp, and the raw materials include a reactant and a perfluorosulfonic acid resin solution.
5. The flexible sheet material according to claim 4, characterized in that: In the raw materials, the mass ratio of the reactant to the perfluorosulfonic acid resin solution is (2-4):
1.
6. A method for preparing a coating layer slurry, characterized in that: The method comprises: (1) mixing a reactant, a perfluorosulfonic acid resin solution, an alcohol and deionized water to obtain a raw material having a viscosity of 100 cp to 1000 cp; (2) The raw materials are subjected to high-speed emulsification and dispersion to obtain a coating layer slurry having a solid content of 20% to 50%, a viscosity of 10 cp to 100 cp, and a particle size of less than 2 μm.
7. The method according to claim 6, characterized in that The active material of the reactant is selected from at least one of platinum, ruthenium, iridium and iridium oxide.
8. The method according to claim 6, characterized in that The linear speed of the high-speed emulsification dispersion is 25 m / s to 60 m / s.
9. The method according to claim 6, characterized in that The mass ratio of the deionized water to the alcohol is 1:(2-5).
10. The method according to claim 6, characterized in that The alcohol is selected from at least one of methanol, ethanol, n-propanol and isopropanol.